Pollen-mediated gene flow from wild carrots (Daucus carota L. subsp. carota) affects the production of commercial carrot seeds (Daucus carota L. subsp. sativus) internationally and in New Zealand in the context of climate change: A systematic review - Asharp, G.; Pieralli, S.; Sofkova-Bobcheva, S.; Ward, A.; McGill, S. (Elsevier, 2024)
Climate change will impact the carrot seed industry globally. One adaptation strategy to limit climatic impacts on the production of commercial carrot seeds is geographical shift. However, production must be shifted to climate-optimal places that are free from weeds such as wild carrots to avoid genetic contamination via hybridization. The process of gene flow between wild and cultivated carrots is critical to enable management of wild carrots in the face of climate change. This review systematically assesses the resilience of wild carrots to climate change and their impact on commercial carrot seed production globally with a focus on New Zealand as a major carrot seed producer. The literature was critically analyzed based on three specific components: i) resilience of wild carrots to climate change ii) genetic contamination between wild and cultivated carrots, and iii) management of wild carrots. The majority of the articles were published between 2013 and 2023 (64.71 %), and most of these studies were conducted in Europe (37.26 %) and North America (27.45 %). Country-wise analysis demonstrated that the majority of the studies were carried out in the United States (23.53 %) and the Netherlands (11.77 %). There was limited research conducted in other regions, especially in Oceania (1.96 %). Spatial distribution analysis revealed that the wild carrot was reported in around 100 countries. In New Zealand the North Island has a higher incidence of wild carrot invasion than the South Island. The findings indicated that the wild carrot is becoming more adaptable to climate change, compromising the genetic purity of cultivated carrots due to pollen flow from wild to cultivated carrots. Therefore, ongoing research will be helpful in developing sustainable weed management strategies and predicting potential geographical invasiveness. This study provides a guide for scientists, policymakers, industrialists, and farmers to control wild carrots and produce genetically pure commercial seeds amid climate change.
Keywords: Cultivar purity; Extreme climate; Hybridization; Invasion; Isolation distance; Weed management